Improvement in refractory heart failure by nephrectomy for renal tumour. (10th February 2012) - Shahzad, Adeel; Powell, Christopher; Etherington, Robert; Somauroo, John
Abstract : Hypoalbuminaemia and anaemia are conditions known to aggravate congestive cardiac failure (CCF). Renal cell carcinoma is often associated with hypoalbuminaemia and anaemia. The authors report an interesting case of a patient with severe refractory CCF who incidentally was found to have a massive renal cell tumour. Clinically, his heart failure was being aggravated by hypoalbuminaemia and anaemia. Despite aggressive diuretic therapy and multiple blood and albumin transfusions, there was no clinical improvement. He subsequently underwent nephrectomy of the renal tumour, with subsequent dramatic clinical improvement in his heart failure. His symptoms resolved completely and he did not require any further diuretic therapy.